Unraveling the Safety Profile of Nanoscale Particles and Materials - From Biomedical to Environmental Applications 2018
DOI: 10.5772/intechopen.71833
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Risk Assessment of Emerging Nanomaterials: Cytotoxicity, Cellular Uptake, Effects on Biogenesis and Cell Organelle Activity, Acute Toxicity and Biodistribution of Oxide Nanoparticles

Abstract: The lack of toxicological data on nanomaterials makes it difficult to assess the risk related to their exposure, and as a result further investigation is required. This chapter presents the synthesis of controlled oxide nanoparticles followed by the evaluation of their safety profile or toxicity (iron, titanium and zinc oxides). The controlled surface chemistry, dispersion in several media, morphology and surface charge of these nanoparticles are presented (transmission electron microscopy, dynamic light scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 82 publications
2
15
0
Order By: Relevance
“…A recent study also reported the antibacterial efficacy of PCL-Gel electrospun membranes but loaded with considerably higher concentrations of ZnO-NPs (5, 15 and 30 w% relative to the total polymer weight) than those in the present study [32]. The use of low antibacterial NPs concentration in GTR membranes is an important finding of the present work, despite NPs are very promising alternative antibacterial agent for medical applications, there are still concerns about the possible long-term side effects of NPs in living beings; thus, it is necessary to limit the concentration of NPs released into the host tissue by using the minimum effective doses [33,67]. Moreover, in future clinical applications, the reduction of the amount of NPs in membranes would reduce their production costs.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…A recent study also reported the antibacterial efficacy of PCL-Gel electrospun membranes but loaded with considerably higher concentrations of ZnO-NPs (5, 15 and 30 w% relative to the total polymer weight) than those in the present study [32]. The use of low antibacterial NPs concentration in GTR membranes is an important finding of the present work, despite NPs are very promising alternative antibacterial agent for medical applications, there are still concerns about the possible long-term side effects of NPs in living beings; thus, it is necessary to limit the concentration of NPs released into the host tissue by using the minimum effective doses [33,67]. Moreover, in future clinical applications, the reduction of the amount of NPs in membranes would reduce their production costs.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…However, there is a considerable lack of information regarding the neurotoxicity of nanomaterials, which complicates risk assessments following exposure. Therefore, the development of rapid, accurate, and effective strategies for determining the neurotoxic effects induced by nanomaterials is crucial [63].…”
Section: Neurotoxicity Of Nanomaterialsmentioning
confidence: 99%
“…It is a general problem that SPIONs tend to be absorbed by liver macrophages. However, this problem could be resolved by appropriately adjusting the particle’s shell—negatively charged PEG used as the coating was shown to increase the liver and spleen uptakes of SPIONs [ 26 ]. Chitosan as the coating material seems to prevent such an interaction [ 27 ].…”
Section: Summary Of Clinical Applications Of Spionsmentioning
confidence: 99%